Hemoglobin A1c in prediabetics: a prognostic indicator of Acute Coronary Syndrome and its Severity - Karki, Biplave; Karki, Sharvya S; Ghimire, Jeet P; Uraw, Surendra; Shah, Prashant; Pandey, Naveen K; Karki, Prahlad (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Diabetes mellitus is a well-recognized risk factor for cardiovascular disease and acute coronary syndrome. However, evidence is limited regarding the prognostic value of ’prediabetes’ on the clinical outcome of ACS. HbA1c reflects average blood glucose concentrations over the previous 2-3 months, and is not affected by stress, hence, can be used in acute clinical situation like ACS. METHODS This was a single center, case control study done in 115 patients, without history of diabetes mellitus, consisting of 71 males and 44 females, admitted with ACS in the Department of Cardiology, BPKIHS, Dharan, Nepal, between August 2020 to July 2021. HbA1c was measured on admission. Patients having HbA1c ≥6.5% (diabetics) were excluded. Patients with HbA1c 5.7-6.4% as prediabetic (cases) and <5.7% as non-diabetic (control) were considered for analysis. The primary endpoint was major adverse cardiac events (MACE) during hospital stay. MACE included CV mortality, urgent vessel revascularization, VT/VF and congestive heart failure RESULTS In this study, among prediabetic (cases) vs non-diabetic (controls), 23.2% vs. 5.4% developed heart failure, 2.3% vs. 2.7% had VT/VF, urgent vessel revascularization was done in 2.3% cases vs 5.4% controls and mortality occurred in 2.3% cases vs. no mortality among controls. There was no significant association between mace and HbA1c but heart failure was significantly higher among cases with HbA1c≥5.7% (p=0.026). CONCLUSION In our study, though HbA1c≥5.7% had no prognostic value for overall mace, it was significantly associated with heart failure in ACS patients.